The Seclusion of Eustochium: Paschasius Radbertus and the Nuns of Soissons. Issue 4 (26th January 2017) - Matis, Hannah W.
Abstract : This article examines three works by the ninth-century theologian, Paschasius Radbertus, all addressed to the Carolingian community of religious women at Notre Dame de Soissons. In addition to being valuable sources for the Mariologist, these sources provide insights into the complex social world of Carolingian religious women. Written at the time of the implementation of the monastic reforms of Benedict of Aniane, Radbert's texts can be read as responses to the imposition of a stricter form of claustration on women's communities. Drawing on the patristic model of Jerome and Eustochium in particular, the spirituality of these texts stresses the contributions of religious women through intercessory prayer, liturgy, and correct doctrine. Radbert alternately emphasizes the important role played by widows in Carolingian religious houses and encourages younger members not to leave the shelter of the religious life. In particular, Radbert's commentary on Psalm 44 (45) meditates on a text that would have been significant at the nuns' consecrations, deliberately employing language that would have paralleled the conventions of secular marriage. In conclusion, Radbert's three texts for Carolingian nuns bear interesting resemblances to twelfth-century Cistercian spirituality.